Identification of Bacillus amyloliquefaciens subsp. plantarum IMV B-7404 strain exometabolites with antifungal activity - Dragovoz, I. V.; Leonova, N. O.; Zelena, L. B.; Rebriyev, V. A.; Аvdeeva L. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Identification of B. amyloliquefaciens subsp. plantarum IMV B-7404 strain exometabolites causing its antifungal activity has been determined. Using the MALDI-TOF mass spectrometry and molecular genetic methods of analysis, it is shown that lipopeptide antibiotics of the researched strain are related to the family of fengycins.